2011
DOI: 10.1016/s1474-5151(11)00115-0
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Based Models for Cardiovascular Disease Prevention from Research to Clinical Practice

Abstract: The worldwide personal and societal costs related to diseases of the vascular system are enormous. International research efforts have focused on discovering ways to implement prevention strategies shown to be both effective and cost-efficient. Teams comprising health care professionals with expertise in nursing, dietetics, physical activity, and behavioral skills have shown high levels of success in preventive efforts, particularly in high-risk and vulnerable populations. Used appropriately, team-based, nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
1
20
0
7
Order By: Relevance
“…There is a large body of evidence showing that lifestyle modification nurse-based programmes effectively improve risk factors and related health behaviours, quality of life, morbidity and mortality in patients with CAD (AHA 2010, Berra et al 2011). No other study has been found that evaluates the effectiveness of an individualised programme to promote self-care in sleep-activity in patients with CAD following treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a large body of evidence showing that lifestyle modification nurse-based programmes effectively improve risk factors and related health behaviours, quality of life, morbidity and mortality in patients with CAD (AHA 2010, Berra et al 2011). No other study has been found that evaluates the effectiveness of an individualised programme to promote self-care in sleep-activity in patients with CAD following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is a largely preventable worldwide disease, and it is important to continue supporting a systematic approach to cardiovascular risk reduction through team-based, nurse-directed management (Berra et al 2011). Patients with CAD often suffer from emotional, cognitive and social disturbances and experience reduced healthrelated quality of life (HRQoL), which, over time, result in failure to adopt a healthy lifestyle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care management is usually provided by nurses and other members of the primary health care team such as dietitians, physiologists, and physical therapists. Underlying principles of nurse case management (NCM) were well defined in a recent review of Nurse-Based Models for Cardiovascular Disease Prevention [12]. These principles apply to all adult populations, including seniors.…”
Section: Innovative Models Of Care For Chronic Illness In Aging Populmentioning
confidence: 99%
“…6. Protocol and guideline-based use of cardioprotective medications must be available for case managers to optimize risk reductions efforts [12].…”
Section: Innovative Models Of Care For Chronic Illness In Aging Populmentioning
confidence: 99%